Case Report: Multisystem inflammatory syndrome in children with associated proximal tubular injury - Orsi, Silvia Maria; Pepino, Carlotta; Rossoni, Lisa; Serafino, Margherita; Caorsi, Roberta; Volpi, Stefano; Palmeri, Serena; Faragli, Alessandro; Lugani, Francesca; Bigatti, Carolina; Ghiggeri, Gian Marco; Verrina, Enrico Eugenio; et al. (Frontiers in Nephrology, 2023)
Introduction SARS-CoV-2 infection in the pediatric population can be associated with a multiorgan inflammatory syndrome called children’s multisystem inflammatory syndrome (MIS-C). The kidneys can be affected by a broad spectrum of possible injuries, whose pathogenetic mechanisms are still unclear. Case report We report the case of a 5-year-old boy with severe cardiac involvement in the context of MIS-C. After two weeks of hospitalization, an abdominal ultrasound showed massive bladder “debris”, followed by the onset of normoglycemic glycosuria. Over time, there was a progressive increase in glycosuria, and the presence of a mat of amorphous phosphate crystals was evidenced on urinary sediment. Together with the findings of hypo-uricemia, increased urinary uric acid, and globally increased urinary amino acids, a clinical picture of kidney proximal tubular damage with secondary Fanconi-like syndrome took shape. Discussion This case report describes the case of a patient with MIS-C with cardiac and kidney involvement characterized by proximal tubular damage, which slowly improved but still persisted at the 8-month follow-up. The pathogenesis of the damage is unclear and probably multifactorial.